2019
DOI: 10.5513/jcea01/20.4.2227
|View full text |Cite
|
Sign up to set email alerts
|

Investment behavior of the Polish farms – is there any evidence for the necessity of policy changes?

Abstract: Investment in agriculture is related to modernization and technological upgrading of agricultural holdings and it influences all the aspects of functioning of farms. Numerous studies proof that investment plays a key role in improving farms' competitiveness and increases their resilience to changes in surrounding. The aim of the paper is to analyze the investment behavior of the Polish farmers. The study was conducted on the basis of the Polish Farm Accountancy Data Network data for the period 2009-2015 and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…The absence of any significant impact of farmer age and education on investment, in contrast to the findings of Niavis et al (2020), suggests that younger and older farmers invest similarly in Hungary. Similarly, the finding that agricultural education does not have a significant effect on investment among Hungarian farmers is not consistent with the findings of Wieliczko et al (2019) in Poland. The current research investigates only the impact of agricultural training and could be extended to include non-agricultural education to get a deeper understanding of the impact of education.…”
Section: Investmentcontrasting
confidence: 69%
See 1 more Smart Citation
“…The absence of any significant impact of farmer age and education on investment, in contrast to the findings of Niavis et al (2020), suggests that younger and older farmers invest similarly in Hungary. Similarly, the finding that agricultural education does not have a significant effect on investment among Hungarian farmers is not consistent with the findings of Wieliczko et al (2019) in Poland. The current research investigates only the impact of agricultural training and could be extended to include non-agricultural education to get a deeper understanding of the impact of education.…”
Section: Investmentcontrasting
confidence: 69%
“…The results of Niavis et al (2020) suggested that the relationship between farmers' age and their investment behaviour was not linear, instead one may observe phases in the life of farmer with different rates of investment. According to Wieliczko et al (2019), education can have a negative impact on investment due to the non-agricultural work undertaken by these farmers which discourages agricultural investment. Fertő et al (2017) identified a positive association between investment and investment subsidies.…”
Section: Investmentmentioning
confidence: 99%